2020
DOI: 10.1088/1757-899x/805/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Improved power conversion efficiency in Perovskite solar cell using silver nanoparticles modified photoanode

Abstract: Metal nanoparticles have demonstrated outstanding properties in photovoltaic devices through introducing localized surface plasmon effects. The performance of Perovskite solar cell (PSC) by incorporating Ag@P4VP NPs was investigated systematically. The plasmonic enhancement effects are explored based on the combination of UV-visible absorption spectroscopy and Scanning Electron Microscope (SEM). The performance, especially the short circuit current density (Jsc), and open circuit voltage (Voc) of the PSC conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The Ag peaks could not be observed in the modified TiO 2 XRD patterns, which indicated that silver was only homogenously distributed on the surface of the TiO 2 [32,33]. These results were consistent with the UV-vis results of our previous studies and that of other authors, where there was also no peak characteristic of silver around 450 nm detected [12,34]. The XRD patterns showed no peak which was not indexed or corresponding to silver oxide phase observed.…”
Section: X-ray Diffractionsupporting
confidence: 88%
See 3 more Smart Citations
“…The Ag peaks could not be observed in the modified TiO 2 XRD patterns, which indicated that silver was only homogenously distributed on the surface of the TiO 2 [32,33]. These results were consistent with the UV-vis results of our previous studies and that of other authors, where there was also no peak characteristic of silver around 450 nm detected [12,34]. The XRD patterns showed no peak which was not indexed or corresponding to silver oxide phase observed.…”
Section: X-ray Diffractionsupporting
confidence: 88%
“…3b-e confirmed the presence of P 4 VP. Very low peak attributable to the element Al may be related to the manipulation of the specimen during SEM investigation [12]. The signal of Si, Ca, Ar and Cd should be attributed to the building element of the substrate since no other Si, Ca, Ar or Cd-based chemicals were used throughout the synthesis.…”
Section: Energy Dispersive X-raymentioning
confidence: 99%
See 2 more Smart Citations
“…Eli et al, provided a systematic analysis of the performance of a PSC synthesized by depositing Ag@P4VP NPs on the TiO2 layer of PSC devices. [ 55 ] The PCE was enhanced by 39.4% compared to the reference cell (from 3.80% to 5.69%). This enhancement is due to a number of reasons, including increase in current density (from 11.04 to 12.61 mA cm2) as the direct contact decreases, improved light absorption, and spectral enhancement of the composite photoanode that developed from the SPR of the AgNPs.…”
Section: Plasmonic Effects In Pscsmentioning
confidence: 99%